Researching Kedah’s Malay heritage food tradition and eating culture - Noriza Ishak; Anida Ismail; Mazni Saad; Adilah Md Ramli (Human Resource Management Academic Research Society (HRMARS), 2021)
This paper presents findings from a study carried out through a qualitative study investigating the various types of Kedah food heritage. A snowball approach was used to collect data from four families in Kuala Nerang, Pendang, and Alor Setar within nine days. Eleven types of food were then grouped into breakfast, main dishes, and snacks/delicacies. The data revealed this food would be able for consumption at any time. The villagers continue to consume the same traditional foods that their families used to cook. These results highlighted the importance of sustaining the preparation of heritage food in coping with the lost identity of the food. This study suggests that the Heritage Department includes the identified foods into the list of National food heritage to preserve these foods as part of the food sustainability initiatives.